The Effect of Code. Org Activities on Computational Thinking and Algorithm Development Skills - OLUK, Ali; ÇAKIR, Recep (Journal of Teacher Education and Lifelong Learning, 2021)
With the sub-skills covered, there are many studies aimed at providing students with computational thinking skills that are known to be an important skill for today's students. In this study, it is aimed to investigate the effect of code.org applications on the development of computer thinking and algorithm development skills of the students. In this study, experimental research design with pre-test and post-test control group was used. A total of 67 middle school of 6th grade students, 32 of who were in the control group and 35 in the experimental group, participated in the study. The study was planned to cover 6 weeks of information technology and software courses with students. The course was enriched with the applications in Code.Org site for the experimental group students. The control group was treated appropriately course curriculum to their students. In the study, the scale of computer thinking skill levels and algorithm development achievement test were applied to the students as pre-test and post-test. When the data obtained in the study is examined, it is seen that there is no significant difference between the pre-test results of algorithm development achievement test and computer thinking skill levels scale. However, when the differences between pre-test and post-test scores of both tests were examined, it was seen that there was a significant difference in favor of the experimental group. As a result, it can be said that code.org applications used by experimental group students have positive effect on developing algorithms and computer thinking skills of students.
Keywords: Alan Eğitimleri; Computational Thinking; Code.Org; Algorithm Development; Other Fields of Education; 4. Education; 3. Good health